THE INSECTICIDAL ACTIVITY OF ESSENTIAL OILS ON EGGPLANT CULTIVARS INFESTED WITH THE COTTON APHID (APHIS GOSSYPII GLOVER (HEMIPTERA: APHIDIDAE)) UNDER GREENHOUSE CONDITIONS - A. S. Khalaf; Q. H. Ahmed (مجلة الأنبار للعلوم الزراعية)
The cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae), is a major pest that causes considerable economic damage worldwide, infesting many vegetable and fruit crops. Due to its developed resistance to chemical pesticides and harm to humans and the environment, it has become necessary to move towards finding alternatives. This study evaluated new nanoemulsion formulations of three essential oils, i.e., thyme (Thymus vulgaris), clove (Eugenia caryophyllus), and lavender (Lavandula angustifolia), against three local eggplant cultivars (Naser, Jawaher, and Barcelona) infested with the aphid. A nanoemulsion pesticide formulation was prepared at a concentration of 20% of the above oils. Then, three concentrations of 1, 5, and 10 ml/L of each essential oil were tested separately against A. gossypii and compared to the Sivanto and Levo-registered pesticides under greenhouse conditions. After 14 days of treatment, the 10 ml/L thyme oil concentration produced significant differences in reducing the population density levels of this pest, followed by cloves and then lavender. This study recommends using thyme, clove, and lavender oils as one of the safe alternatives for pest management and to achieve one of the goals of sustainable development